The Organizational Justice Prevailing in Jordanian Universities and its Relationship with Organizational Confidence From Faculty Staff Members' Point of View - Darawsheh, Najwa (Jordan Journal of Educational Sciences, 2017)
The study aimed to examine the organizational Justice prevailing at Jordanian Uni-versities and its relationship organizational confidence from faculty staff members' point of view. The sample of the study consisted of (378) Faculty staff members teaching at Jordanian universities . To achieve the aim of the study, a questionnaire of (32) items was used. One of the main results of the study was that the level of organizational justice was medium, while the level of organizational trust was high. The results of the study also showed statistically significant differences at (α=0.05) in the organizational Justice due to university type, in favor of the governmental staff member and according to the rank in favor of the professor. The results of the study also showed that there were no statistically significant differences (α=0.05) in the organizational trust due to the type of the university, rank and gender. Also, there was positive correlation relationship between the Justice organization and organizational trust